The effectiveness of bariatric surgery on long term psychosocial quality of life – A systematic review. Issue 3 (May 2016) - Jumbe, Sandra; Bartlett, Claire; Jumbe, Samantha L.; Meyrick, Jane
Summary: Background: Little is known about the psychological effects of bariatric surgery. This review aimed to assess long term effectiveness of bariatric surgery on psychosocial quality of life (QoL) of obese adults compared to non-surgical interventions. Methods: A systematic review of the literature was conducted, six electronic databases, plus other relevant sources were searched from inception to January 2014. The main outcome sought was a QoL measure with a minimum 12 months follow-up. Three reviewers screened records, extracted data and independently read through full articles for eligibility and quality using standardised forms. Findings were analysed using narrative synthesis. Results: Of 4383 identified references included in the review, 11 studies showed bariatric surgery to be effective long term for overall QoL than non-surgical treatments with specifically modest benefits psychosocially. Significant improvements in psychosocial QoL alongside improved physical QoL were observed after 2 year follow-up post-surgery compared to non-surgical interventions. However improvements in psychosocial QoL after surgery at 10 year follow up were minimal when compared to non-surgical interventions. When compared to untreated control groups, long term psychosocial QoL did not improve after bariatric surgery despite major improvements in physical QoL, significant weight loss and co-morbidities. Conclusions: Results on long term psychosocial QoL remain uncertain with some suggestion of psychological disorder persisting. This highlights need for psychological intervention post-surgery and further research to provide more data on long-term psychosocial QoL following bariatric surgery.